2016
DOI: 10.1111/ajsp.12142
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of pro‐environmental consumption intention in rural China: The role of traditional cultures, personal attitudes and reference groups

Abstract: This study aimed to identify social-psychological predictors of pro-environmental consumption intention in rural China. To this end, a proposed conceptual model was tested by analyzing the survey data derived from 972 rural respondents in Jiangxi province in south-eastern China. Results showed that the endorsement of traditional cultures (man-nature orientation and collectivism) was linked with pro-environmental consumption behaviuor, but was mediated by intentions. Personal attitudes (environmental cognition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 38 publications
(75 reference statements)
1
20
1
4
Order By: Relevance
“…In addition, we have also found an interesting trend: the amount of variance accounted for by the search for meaning was more than the presence of meaning on various indicators of life satisfaction and mental health, which is the opposite trend compared to Western subjects (Steger et al, 2009). The results suggest that search for meaning may be an important personality trait for Chinese students who have grown up under the Confucian philosophy of san bu xiu ( ) or the 'three indestructibles' (see Liu et al, 2015;Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, we have also found an interesting trend: the amount of variance accounted for by the search for meaning was more than the presence of meaning on various indicators of life satisfaction and mental health, which is the opposite trend compared to Western subjects (Steger et al, 2009). The results suggest that search for meaning may be an important personality trait for Chinese students who have grown up under the Confucian philosophy of san bu xiu ( ) or the 'three indestructibles' (see Liu et al, 2015;Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…For example, Nguyen et al () argue that the cultural values of collectivism and the long‐term perspective of consumers have significant influence on consumers’ purchasing intention for environmentally friendly products. Wang et al () have also demonstrated that a human–nature perspective as well as values of collectivism function as determinants in environmentally friendly consumption intention. As for Chinese consumers, the Doctrine of the Mean is rooted in their traditional culture and is linked with their green purchasing intention.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…The philosophy also encompasses principles that promote self-restraint and long-term development (Chang & Yang, 2014;Chou, Chu, Yeh, & Chen, 2014;He, 2011;Ji, Lee, & Guo, 2010;Yang, 2001Yang, , 2010. Notably, collectivism and an emphasis on harmony between nature and human kind are fundamentally related to green purchasing intention (Chan, 2001;Wang et al, 2016). Moreover, the principles of self-restraint and long-term development have also been recognized as drivers for behaviour in consumption that is environmentally friendly (Chuang, Xie, & Liu, 2016;Nguyen, Lobo, & Greenland, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A fact which causes them to give into peer pressure. Peer influence is generally defined as the extent to which attitudes, beliefs, and actions of an individual are influenced by peers (Sheu and Wang et al, 2016;Wang, 2016;Makgosa and Mohube, 2007;Asubonteng et al, 1996;Armistead, 1985). Furthermore, peer pressure is the direct or indirect influence that is exerted on a peer group, observers or individuals who encourage others to change their attitudes, values, or behaviors to conform to groups as a socially acceptable behaviour under it (Gulati, 2017;Akar et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, a reference group is a group of people whose values and attitudes are considered through direct interaction (Wang et al, 2016;Liang, 2017;Gheorghiu et al, 2015;Sisa and Theuns, 2014;Gillani, 2012;Turcinkova and Moisidis, 2011;Chang et al, 2011;Bearden and Etzel, 2001). Referents with high credibility, such as those having presumed expertise, will often serve as sources of information-based influence for uncertain or uninformed consumers.…”
Section: Literature Reviewmentioning
confidence: 99%